Early diagnosis of melanoma by surface microscopy (dermatoscopy) - Paschoal, Francisco Macedo (São Paulo Medical Journal, 1996)
The main objective of surface microscopy is the early and accurate diagnosis of melanoma in its initial phases of evolution and infiltration. Since the development of the dermatoscope in the 1990’s, surface microscopy has become a simple technique. Differential diagnosis of pigmented skin lesions can be achieved with a diagnostic sensitivity of about 90 percent, and the proper differentiation of pigmented melanocytic and non-melanocytic lesions, and malignant and benign melanocytic lesions, may also be safely determined.